(3GdefJNH ef GdefJNH aj GdfhHs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHf GdLhRi GdMeO ddg Ydi MeOg hUdhGJg Ydi QShdg CeG HYO aEfi deG QSeJ cJGHi GdehShe HGdefJNH ai GdfhH GdaUd GdChd ai bhdg JYGdi hEP bGd QHc ddedGFcI Efi LGYd ai GdGQV NdjaI s
(3BNQgG (B:s
(3gPG cJGH ef QShd Gddg Mjf GLGH Edi GdESdGe hNdY GdcaQ hYHGOI GdGUfGe aEfi Pdc hbJd cGaQG bO CHj GdESdGe hgPG eG GfJgi GdjfG ef EJeGe gPG GdcJGH s
(3HgG fXGe GdJYbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YfjRI GdhWfjI HGdLGeY GdcHjQ s
Keywords: (3CUhd Gdabgs